Understanding Misogynistic Hadiths from The Perspective of Fazlur Rahman’s Double Movement Hermeneutics: Memahami Hadis Misoginis dalam Perspektif Hermeneutika Gerakan Ganda Fazlur Rahman - Sugiara, Lalu Rahmat; Salsabila Arju; Yogi Sopian Haris (Jurnal Living Hadis, 2025)
Gender issues constitute a prominent area of inquiry in Islamic studies, particularly about the interpretation of hadith. This is due to the frequent portrayal of women in subordinate positions within patriarchal constructions, including in the interpretation of hadith texts. Several hadiths are even perceived to carry misogynistic discourse, raising critical questions regarding gender justice in Islam. Departing from this discourse, this study formulates two main research questions; first, how can the contextualization of hadiths considered misogynistic be understood within Islam? second, how can Fazlur Rahman’s double movement hermeneutical approach aid in interpreting such hadiths?Utilizing a literature review method and a qualitative-descriptive approach, this research explores the dialectical relationship between the original socio-historical context in which the hadiths were revealed and the universal principles that may be derived to address contemporary challenges. The findings indicate that the emergence of misogynistic views is largely influenced by conservative scholars’ interpretations, which often rely on sacred texts as ontological foundations. These interpretations tend to neglect the socio-historical aspects accompanying the hadiths’ emergence, especially significant in a modern era characterized by fundamentally different social constructs. Therefore, hadiths deemed misogynistic need to be reinterpreted more justly through a socio-cultural lens grounded in the Prophet’s time, as well as through universal ethical values aligned with the spirit of maqāṣid al-syarī‘ah.